The Influence of the Leadership Style of the Head of the Health Center on the Performance of Health Workers in the Health Center: Literature Reviews - Masni, Fenny Ratna (EDUCARE: Jurnal Pendidikan dan Kesehatan, 2025)
Leadership is an important element and determines the smoothness of health center services because leadership is the core of organizational management. This study aims to determine how much influence the leadership style of the head of the health center has on the performance of health workers in the health center. The method used is a literature review by using two online databases, namely Google and Google Scholar. The search was limited to journals published between 2012 and 2023, which are available in Indonesian. The results of the study show that from the various journals used as references, leadership style has a crucial role in creating positive changes in building the quality of health workers, the work environment, improving the quality of public services, and overall organizational performance. The conclusion in this study shows that there is an influence of leadership style, transactional, transformational and situational on the performance of health workers. is expected to provide an overview of the maximum leadership qualities to improve the quality of health worker performance to take further policies.